2007
DOI: 10.1097/iop.0b013e31804bdf0c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of External Dacryocystorhinostomy on Surgical Outcome

Abstract: In experienced hands, external DCR has good postoperative success with a low complication rate. Early DCR does not have a substantial advantage over late surgery with regard to surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The mean duration of symptoms was 2.7 years. Studies by Erdol 6 et al and Seider et al 7 suggest that duration of obstruction is a predictive factor for external DCR success rates with earlier surgery offering a greater chance of success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean duration of symptoms was 2.7 years. Studies by Erdol 6 et al and Seider et al 7 suggest that duration of obstruction is a predictive factor for external DCR success rates with earlier surgery offering a greater chance of success.…”
Section: Discussionmentioning
confidence: 99%
“…2 Various studies conducted have shown that surgical success co-relates with factors like patient age, duration of obstruction and presence or absence of previous episodes of dacryocystitis. 6,7,8 The aim of this study was to evaluate the pre-and postoperative characteristics and surgical outcomes in patients who underwent DCR in our tertiary care centre. …”
mentioning
confidence: 99%
“…Seideret al [1] found that patients who had longer lasting symptoms of chronic dacryocystitis had lower success rate. Main drawback of this study stems from the fact that information about the patient's disease was taken from their medical charts and the duration of epiphora was self-reported by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Primary benefits of External DCR are that it is a faster and easier surgery to perform. The surgical success rate [1] was found to correlate with the duration of obstruction and patient's age. The success rate was lower when the obstruction lasted longer and the patient was younger.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation